Asset Returns and the Listing Choice of Firms - Baruch, Shmuel; Saar, Gideon (Review of Financial Studies, 2009)
[We propose a mechanism that relates asset returns to the firm's optimal listing choice. We use a theoretical model to show that a stock will be more liquid when it is listed on a market where "similar" securities are traded. We empirically examine the implications of our model using New York Stock Exchange (NYSE) and Nasdaq securities. We find that the return patterns of stocks that switch markets become more similar to the return patterns of securities listed on the new market prior to the switch. Stocks that are eligible to switch but stay put are more similar to securities listed on their market than to securities listed on the other market. Our results suggest that managers make listing decisions that enhance the liquidity of their firms' stocks]